Retreatment with PARPi following stem cell transplant in a patient with recurrent ovarian cancer and myelodysplastic syndrome - Shilpa Mokshagundam; Mrinal M. Patnaik; Luigi A. DeVitis; Simrit K. Warring; Megan E. Grudem; Matthew S. Block (Gynecologic Oncology Reports)
Objective: As the use of poly(adenosine diphosphate–ribose) polymerase inhibitors (PARPi) increases in the management of advanced ovarian cancer, therapy-related myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) may be observed more frequently. Strategies for management of this unique condition are needed. Methods: In this case report, we demonstrate the case of a patient with advanced ovarian cancer and a pathogenic BRCA1 mutation who developed MDS following 4 years of maintenance PARPi. Results: Management of therapy-related MDS/AML is variable. In addition, subsequent oncologic treatments may be limited due to risk of MDS/AML recurrence with exposure to cytotoxic therapies and/or PARPi. Risk for MDS/AML recurrence can be monitored and predicted by evaluation for clonal hematopoiesis. This patient underwent autologous stem cell transplant. After subsequent disease recurrence, she underwent repeat germline testing which showed BRCA1 wildtype. In addition, no clonal hematopoietic clones were identified using a specialized institutional assay. For this reason and given previous durable response to PARPi, the patient was re-treated with a PARPi. Conclusions: This case highlights the unique management of therapy-related MDS/AML and underscores the importance of multidisciplinary care in determining safety of subsequent cancer-directed therapies in this patient population.